Crime prevention through environmental design and its challenges in reducing crime: A case of Selangor, Malaysia - Rajadurai, Shamir (PALGRAVE MACMILLAN LTD, 2022)
Crime Prevention through Environmental Design (CPTED) is a crime prevention strategy used in many advanced states to safeguard community members from criminal activities. In a non-western setting of Malaysia, individual selected states apply the system to control their crime occurrences. Despite its implementation throughout its municipal councils in the states, Selangor still has the highest recorded crime rates throughout Malaysia. A few factors and underlying issues have caused high crime rates despite the implementation of CPTED. This paper highlights three of those issues: the misunderstanding of the CPTED concept, insufficient funding, and lack of police involvement in designing the CPTED application. The study aims to understand further the theories of CPTED and ways of practical implementations. The study's research approach is qualitative. The study found that most projects are designed by people that do not understand CPTED entirely; due to the yearly budget limitations, it has limited CPTED application and strategies, and the police have not been included in the CPTED design process. Addressing these issues deliver the long-term social and economic benefits to the community. At a larger scale, the country and CPTED strategies, which are well designed, reduces cost and increases the quality of life for its residents.